Analisis Saham di Pasar Modal Indonesia: Kinerja, Tantangan, dan Prospek Masa Depan - Nadjima, Aulia Rachmatullah; Andhiyo, Immanuel Given Bintang; Putra, Alfarel Endito (Media Hukum Indonesia (MHI), 2024)
The Indonesian capital market has an important role in the country's economic activities, with its performance highly dependent on national, regional and international economic performance. This analysis provides a holistic picture of the performance of leading stocks, the dynamics of stock trading, and the driving factors in the capital market. This research explores what factors drive a significant increase in leading shares, including external factors such as changes in the global investment climate, national economic developments, and government policies that affect related sectors. Apart from that, internal aspects of the company such as financial performance, innovation and management strategy are also considered. Challenges faced by the Indonesian capital market include the limited types of securities traded, regulations for protecting investor rights, "gaming" in stock transactions, and the public's lack of knowledge about the capital market. To improve capital market performance, the role of local investors needs to be increased, and several challenges in capital market development must be overcome. The future prospects of the Indonesian capital market depend on the ability of policy makers to take advantage of existing opportunities. Thus, this analysis provides a better picture of the performance of leading stocks, the dynamics of stock trading, and the driving factors in the capital market, as well as offering recommendations for improving capital market performance in the future.